Analysis Influence of Proactivity Power Business, Market Orientation, and Competitive Advantage toward Marketing Performance - Fitriani, Lili Karmela (APMBA (Asia Pacific Management and Business Application), 2015)
This research is an empirical study on Batik SMEs (Small Medium Enterprises) in Cirebon District, West Java. This study analyzes the effect of proactivity power business, market orientation, and competitive advantage towards marketing performance. The subjects of this research were 215 Batik SMEs in Cirebon District West Java. The analysis was done using Structural Equation Modeling (SEM), AMOS ver. 18. The result shows that proactivity power business, market orientation, and competitive advantage give positive influence on marketing performance ofÂ  Batik SMEs. The research implication is when SME businesses focus on the effort in improving their proactivity power business and competitive advantage, it will give positive impact on marketing performance. Other research finding reveals thatÂ  the orientation of customer and orientation of competitor have some effects on marketing performance. In addition, SME businesses should know what customers want and they should be able to identify their competitors in order to improve their marketing performance.Â